Innovative Exercise in a New Normal (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Innovative exercise is an important aspect of a healthy lifestyle. The availability of various resources has made it easier for people to find activities that they enjoy and that meet their fitness goals. In addition to traditional exercises like running, weightlifting, and yoga, there are also new, exciting forms of exercise such as virtual reality fitness, aerial yoga, and trampoline workout classes. Technology has also played a major role in making exercise more accessible and convenient. For example, there are fitness apps that allow users to track their progress, set goals, and participate in virtual workout classes from the comfort of their own homes. Wearable fitness devices, such as fitness trackers and smartwatches, make it easy to monitor physical activity and track progress in real-time. In addition to these technological advancements, there is also an increased focus on making fitness facilities more inclusive and accessible to all. This includes the incorporation of accessible equipment, sensory-friendly environments, and adaptive fitness programs for individuals with disabilities. Overall, the trend towards innovative exercise is not only providing people with new and exciting ways to stay active, but it is also helping to address the challenges posed by the pandemic and other emerging health threats. By continuing to evolve and adapt to changing circumstances, the fitness industry is playing an important role in promoting health and wellness for people around the world.